(3MGTjI edG YHO Gddgs - (3YHO Gddg GdCUagGfjs ((3WgQGfs)
(3ChdgG (B:s
.. (3Cj GdGjUGd Edi GdeWdhH hbjd gj EQGOI GdWQjb Cj GdehUd Edi GdeWdhH hGdaQb Hjf gPjf GdeYfjjf Cf GdGhd jSJdRe GdhUhd Edi GdeWdhH HNdGa GdKGfj aEf GdOdGdI Ydi dGeG jhUd Edi GdeWdhH dG jdRe Cf Jchf ehUdI (B...s
(3BNQgG (B:s
... (3bhdg hgPG HGdeaGUd CTHg Cj GdCeQ GdKGfj CTHg HebGUO Gdaf efg HebOeGJ hdPG JQi GdeJCNQjf deUGMH GdeWGdY (B..(3bhdg LYdfG Gddg hEjGce ef GdQGSejf aj GdCeQjf hQRbfG HaVdg hLhOg SYGOI GdOGQjf (B.. (3hbO Je GdcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3eMeO QVG GdeXaQjs
Keywords: (3GdadSaI hGdefWbs